Differences in neuromuscular qualities between speed and technical Italian elite alpine skiers - Federico, D.; Andrea, B.; Roberto, M.; Andrea, P.; Nicola A. M.; Ermanno, R. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: High levels of lower limb strength have been suggested to be an important factor for competing in top-level alpine skiing. However, SPEED and technical (TECH) disciplines have different characteristics that may require specific neuromuscular qualities. Therefore, the aim of this study was to compare lower limb force control and fatigability between SPEED and TECH elite alpine skiers.